Quantification of mast cells in oral reactive lesions - an immunohistochemical study: Mast cells in oral reactive lesions - Baddireddy, Sita Mahalakshmi; Akula, Satya Tejaswi; Nagilla, Jithender; Manyam, Ravikanth (Acta Biomedica Atenei Parmensis, 2022)
Background: Reactive lesions (RLs) are the most common oral mucosal lesions that are benign in nature and are more likely to reoccur if the lesion or local irritants at the site are not completely removed. The histopathology is usually determined by the stage of the lesion, which includes neovascularization, inflammation, and fibrosis etc. Aim: To evaluate and compare mast cell counts in different reactive lesions with normal gingiva (NG) and to determine the correlation between mast cell count and inflammation, fibrosis, and angiogenesis using immunohistochemistry. Materials & Methods: 10 pyogenic granulomas (early and late), 10 irritational fibromas, 5 inflammatory fibrous hyperplasia, and 5 peripheral cemento-ossifying fibromas 5 normal gingiva were evaluated. Mast cell counts were compared. ANOVA and t-tests were used to analyze the data. Spearman correlation was used to compare the mast cell count to the inflammation, fibrosis, and vascular components. A p-value of 0.05 was considered statistically significant. Results: The mean number of mast cells were increased in oral reactive lesions when compared to NG. Although mast cells were significantly higher in IFH and IF, there was no correlation found among mast cells and fibrosis/inflammation/vascularity. Conclusion: Reactive process involves multiple interactions among mast cells, endothelial cells, fibroblasts, and other immune cells, among which the role of mast cells has been evaluated. Mast cell count increases in these reactive lesions, possibly reflecting an important role in microenvironment modification, but it is not the sole cause of these lesions’ pathogenesis.